Comparison of the efficacy of spinal cord stimulation and dorsal root ganglion stimulation in the treatment of painful diabetic peripheral neuropathy: a prospective, cohort-controlled study - Han, Yu-Fei; Cong, Xi (Frontiers in Neurology, 2024)
Objective The aim of this study was to compare the clinical outcomes of spinal cord stimulation (SCS) and dorsal root ganglion stimulation (DRG-S) in the treatment of painful diabetic peripheral neuropathy (PDPN). Methods In this prospective cohort study, 55 patients received dorsal column spinal cord stimulation (SCS group) and 51 patients received dorsal root spinal cord stimulation (DRG-S group). The primary outcome was a Numerical Rating Scale (NRS) remission rate of ≥50%, and secondary outcomes included the effects of SCS and DRG-S on quality of life scores (EQ-5D-3L), nerve conduction velocity, and HbA1c, respectively. Results The percentage of NRS remission rate ≥ 50% at 6 months was 80.43 vs. 79.55%, OR (95% CI): 1.06 (0.38–2.97) in the SCS and DRG-S groups, respectively, and the percentage of VAS remission rate ≥ 50% at 12 months was 79.07 vs. 80.95%, OR (95% CI): 0.89 (0.31–2.58). Compared with baseline, there were significant improvements in EQ-5D and EQ-VAS at 6 and 12 months (p < 0.05), but there was no difference in improvement between the SCS and DRG-S groups (p > 0.05). Nerve conduction velocities of the common peroneal, peroneal, superficial peroneal, and tibial nerves were significantly improved at 6 and 12 months compared with the preoperative period in both the SCS and PND groups (p < 0.05). However, at 6 and 12 months, there was no difference in HbA1c between the two groups (p > 0.05). Conclusion Both SCS and DRG-S significantly improved pain, quality of life, and lower extremity nerve conduction velocity in patients with PDPN, and there was no difference between the two treatments at 12 months.